2021
DOI: 10.1097/qad.0000000000003093
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery plaque progression and cardiovascular risk scores in men with and without HIV-infection

Abstract: Objective: The aim of this study was to assess the association of cardiovascular disease (CVD) risk scores and coronary artery plaque (CAP) progression in HIV-infected participants.Methods: We studied men with and without HIV-infection enrolled in the Multicenter AIDS Cohort Study (MACS) CVD study. CAP at baseline and follow-up was assessed with cardiac computed tomography angiography (CCTA). We examined the association between baseline risk scores including pooled cohort equation (PCE), Framingham risk score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…[3][4][5] Cardiac imaging in PLWH has typically relied on carotid ultrasound for measurement of carotid intima-media thickness (IMT), [6,7] and non-contrast CT for detection of coronary artery calcification (CAC). [8][9][10][11] More recently, in PLWH, we [10,11] and others [12][13][14] have applied coronary CT angiography (CCTA), which can detect not only calcified but also non-calcified plaque including high risk coronary plaque. CCTA is of particular interest in the setting of PLWH, because coronary plaque in younger persons typically is non-calcified [15] and the median age of many Western populations of PLWH is around 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Cardiac imaging in PLWH has typically relied on carotid ultrasound for measurement of carotid intima-media thickness (IMT), [6,7] and non-contrast CT for detection of coronary artery calcification (CAC). [8][9][10][11] More recently, in PLWH, we [10,11] and others [12][13][14] have applied coronary CT angiography (CCTA), which can detect not only calcified but also non-calcified plaque including high risk coronary plaque. CCTA is of particular interest in the setting of PLWH, because coronary plaque in younger persons typically is non-calcified [15] and the median age of many Western populations of PLWH is around 50 years.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 Indeed, studies comparing participants with or without HIV infection found that traditional risk models for CAD, such as pooled cohort equations (PCEs) or Framingham Risk Scores, 7 are frequently inaccurate among PWH compared with the general population. 8 , 9 The mechanisms driving the excess risk are poorly understood. Therefore, there is a critical need to develop improved strategies to predict ASCVD in this population, and to identify asymptomatic PWH at greatest risk for future ASCVD to guide preventive measures.…”
mentioning
confidence: 99%
“…Coronary computed tomography angiography (CCTA) has emerged as a powerful tool to extract surrogate indices for clinical CAD risk to assess such novel biomarkers. 8 , 20 , 21 …”
mentioning
confidence: 99%
“…First, baseline CVD risks are low for cART-naı ¨ve PWH. The Multicenter AIDS Cohort Study (MACS) established that failure of viremic control in those on cART is a key correlate of CVD, as characterized by cardiac plaque progression [8]. But, the large D:A:D (Data Collection on Adverse Events of Anti-HIV Drugs) study found no increase in at least certain types of CVD, including acute myocardial infarction, in the absence of cART [9].…”
mentioning
confidence: 99%